A Democratic Candidate,' Harper's Weekly caricature, 1906 (Harper & Brothers, 1906)
Issue of 'Harper's Weekly, A Journal of Civilization' (volume L (volume 50), no. 2600) political magazine featuring a caricature of William Randolph Hearst as a mudslinging scarecrow/straw-man stuffed with his sensational newspapers. In the illustration he throws mud at other known Democratic politicians and nominees including Bailey, Tillman, Jerome, John Sharp Williams, Parker, Cleveland, McClellan" while bullfrogs Conners and Murphy look on covered in brass checks. The text beneath reads "A Democratic Candidate" while the back features commentaries. Circa October 20th, 1906.